Kolaborasi Pemerintah dan Perguruan Tinggi dalam Pengabdian Masyarakat Berbasis SDGs - Tri Dava Kurniawan; Nayif Achmad Fannur; Firre An Suprapto; Indah Prabawati (CV. Lentera Literasi Indonesia, 2026)
This study examines the implementation of collaboration between government entities and higher education institutions in community service programs and its contribution toward achieving the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 17 (Partnerships for the Goals). The central problem is the persistently low effectiveness of such collaboration, evidenced by institutional role disparities, policy-practice misalignments, and limited program sustainability. A quantitative descriptive method was employed by systematically analyzing 45 community service program reports published in accredited journals between 2019 and 2025. Data were gathered through structured coding sheets and processed using descriptive statistics. Results reveal a mean collaboration effectiveness score of 3.2 (moderate category). The widest gaps were recorded in role equality (2.9) and post-assistance program sustainability (2.7). While 73% of programs improved short-term technical capacity, only 31% produced lasting economic independence outcomes. The study concludes that a paradigm shift is necessary moving from top-down interventions toward a participatory pentahelix collaboration model that integrates digital technology and social capital reinforcement.